Towards a Grammar of the Idea of North: Nordicity, Winterity - Chartier, Daniel (Nordlit, 2007)
The imaginary of North, in the Western world of the imagination, refers to a series of figures, colours, elements and characteristics conveyed by narratives, novels, poems, films, paintings and advertising which-from the myth of Thule to contemporary representations in popular culture-have forged a rich, complex network of symbolic meanings. The "North" poses the problem of the relationship between geographic realities and the world of the imagination, since those who have written and read about it in Europe and America, have, for the most part, never been there. Representations of "North" are discovered like layers of discourse, laid down by different cultures, and picked up on and shaped by different aesthetic movements.